Tuning Sn3O4 for CO2 reduction to formate with ultra-high current density. (November 2020) - Liu, Li-Xia; Zhou, Yang; Chang, Yu-Chung; Zhang, Jian-Rong; Jiang, Li-Ping; Zhu, Wenlei; Lin, Yuehe
Abstract: In light of environmental concerns and energy demand, significant progress has been made toward CO2 reduction with high activity and selectivity. Particular interest has been focused on liquid products because of the easier separation process and higher value comparing to traditional gaseous products. Formic acid (or formate) can be one of the most economically viable reduction products. Nevertheless, few catalysts can meet the requirement for commercial-viable production, especially the current density. Herein, a hierarchical-Sn3 O4 nanosheet (H–Sn3 O4 NS) electrocatalyst is synthesized and applied into a three-compartment CO2 flow cell electrolyzer with ultra-high current density. The as-synthesized H–Sn3 O4 NS electrocatalyst enables electrochemical CO2 reduction to formate with the selectivity of 91.1% at −1.02 V versus reversible hydrogen electrode (RHE) as well as a partial current density of 421 mA cm −2, whose performance is among the best that has been reported for CO2 electrocatalysts. The superior performance is due to the three-dimensional (3D) hierarchical structure, which supplies a large electrochemical surface area (ECSA) to facilitate mass and charge transfer. And the stability study with in-situ Raman spectroscopy and XRD characterization exhibited that the Sn3 O4 materials could still maintain its original oxidation state under the maximum formate Faradaic efficiency of CO2 reduction reaction (CO2 RR). The further theoretical calculation shows that the catalyst surface is beneficial for the formation of OCHO* (the intermediate of formate) than COOH* (the intermediate of CO) or H* (the intermediate of H2 ), which is in favor of the high activity and selectivity for formate in the experiments. Graphical abstract: The synthesized 3D hierarchical-Sn3 O4 nanosheet electrocatalyst enables electrochemical CO2 reduction to formate with the selectivity of 91.1% at −1.02 V (versus reversible hydrogen electrode) as well as a partial current density of 421 mA cm −2, whose performance is among the best that has been reported for CO2 electrocatalysts. Image 1 Highlights: Hierarchical Sn3 O4 NSs are synthesized as CO2 RR electrocatalysts for the first time. The as-prepared catalysts show remarkable performance due to its ingenious structure. A ultra-high formate current density of 465.1 mA cm −2 was obtained at −1.02V vs RHE. DFT calculations show that the catalyst surface is beneficial for the formation of OCHO*.